Wetlands construídos verticais de fluxo ascendente integrado com célula combustível microbiana aplicados no tratamento de esgoto sanitário - Lopes, Paula Tatiany Mendes (2021)
In this study, it was evaluated the behavior of a set of Vertical Upflow Constructed Wetlands (CW), in what refers to the influence of the height of the filtering mass, composed of construction waste, in the removal of organic matter in terms of COD, before and after the insertion of a microbial fuel cell (MFC). The systems were operated continuously, with hydraulic detention time (HDT) of 24 and 48 hours and divided into four stages: E1 (HDT 48 hours, without MFC), E2 (HDT 24 hours, without MFC), E3 (HDT 24 hours, with MFC) and E4 (HDT 48 hours, with MFC). The set consists in three Cws with the following heights of filtering mass: 1.56 m in CW1, 0.70 m in CW2 and 0.44 m in CW3. For each CW, parameters of temperature, pH, dissolved oxygen, turbidity, Total Nitrogen Kjeldahl, Ammoniacal Nitrogen, nitrite, nitrate and total phosphorus were evaluated. The vegetation cover, vetiver grass, had Total Nitrogen evaluated in its leaves and roots. The filtering mass, composed of fragmented brick waste, underwent phosphorus desorption analyzes at the end of the operation. In addition, a sample was collected for analysis of the bacterial community present in each of the systems. CW1 showed greater removal of carbonaceous matter in terms of COD in the stages, reaching an average removal of 70% in E2. Regarding total phosphorus removal, E1 and E4 stood out reaching an average of 41% and 40% removal efficiency in WC1, respectively. CW1 was the system with the highest NTK and N-Amon removal efficiency in E1, with an average of 31 and 46% respectively. Vetiver grass absorbed about 260 g of NT in WC3 during the entire period of operation, representing 30% of the removal of this nutrient in this CW. The total phosphorus adsorbed by the filtering media, during the entire operation, in CW1 reached 29 g. Proteobacteria was the most abundant phylum in all samples, reaching 51.6% in CW1 and 60% in CW2 and CW3, followed by Firmicutes and Acidobacteria. CW1 was the system with the highest values of recovered energy, with an average of 106.1 mV at E3 and 117.8 mV at E4.